2020
DOI: 10.1002/ca.23565
|View full text |Cite
|
Sign up to set email alerts
|

Kambin's triangle and the position of the dorsal nerve root in the lumbar neural foramen

Abstract: Introduction: As a result of the increased utilization of neurosurgical arthroscopic techniques, investigations into population and sex-specific trends of anatomical considerations have become increasingly important. This study aimed to investigate and describe aspects of the neuroanatomical morphometry of lumbar spines in a cadaveric and magnetic resonance imaging (MRI) sample. Materials and Methods: Twenty white adult (>18 years) cadavers (9 males; 11 females) were obtained under Ethical clearance. The lumba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…On the one hand, transforaminal ligaments in the lumbar intervertebral foramen, such as the superior and inferior costotransverse ligaments, which are mostly distributed in the L5-S1 neuroforamen, may influence the L5 nerve root during the reduction process [ 24 ]. On the other hand, extra-foraminal motion of the L5 nerve root during patient positioning could also contribute to a stretch injury of the L5 nerve root due to nerve excursion and displacement of intrathecal nerve roots [ 2 , 12 , 18 ]. Osteophytes arising from the lower L5 and upper S1 may also contribute to the development of postoperative L5 palsy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, transforaminal ligaments in the lumbar intervertebral foramen, such as the superior and inferior costotransverse ligaments, which are mostly distributed in the L5-S1 neuroforamen, may influence the L5 nerve root during the reduction process [ 24 ]. On the other hand, extra-foraminal motion of the L5 nerve root during patient positioning could also contribute to a stretch injury of the L5 nerve root due to nerve excursion and displacement of intrathecal nerve roots [ 2 , 12 , 18 ]. Osteophytes arising from the lower L5 and upper S1 may also contribute to the development of postoperative L5 palsy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…König et al examined L1-5 levels in 20 cadavers and found that L2-3 was larger than L3-4 (181.2 mm 2 vs 172.2 mm 2 ). 4 Additionally, in Hardenbrook et al's analysis of 8 cadavers, L1-2 (175 mm 2 ) was larger than both L2-3 (172 mm 2 ) and L3-4 (171 mm 2 ). 11 On the other side, Lertudomphonwanit et al found that L1-2 (100.23 mm 2 ) was larger than L2-3 (98.73 mm 2 ).…”
Section: Area Of Kambin's Trianglementioning
confidence: 94%
“…For this reason, there have been differences regarding the exact definition, sizes, and anatomical limits of Kambin's triangle. [4][5][6][7][8][9][10][11][12] ABBREVIATIONS ENR = exiting nerve root; MISS = minimally invasive spine surgery; PRISMA = Preferred Reporting Items for Systematic Reviews and Meta-Analyses; SAP = superior articular process.…”
mentioning
confidence: 99%
“…Finally, the size and shape of the inferior triangle are known to be highly variable and sensitive to adjacent spinal pathology such as facet hypertrophy, disk herniation, and loss of disk height. [45][46][47] In some patients, the inferior triangle may be no more than a theoretical space, without any appreciable surface area between the exiting nerve root, the superior endplate of the adjacent vertebral body, and the facet joint. 45 Thus, successful TFESI via the inferior triangle may impair epidural contrast spread and present additional technical challenges above and beyond the safe triangle approach, while not necessarily obviating intravascular injection.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%